2009
DOI: 10.1039/b820204d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of quantum dot–polymer composites

Abstract: In this study, we demonstrate a facile and simple synthesis of quantum dot (QD)-polymer composites. Highly fluorescent semiconducting CdSe/ZnS quantum dots were embedded in different commercially available polymers using one easy step. QD-polymer composite nanoparticles were also synthesized using template-assisted synthesis. In particular, we self-assembled lamellar micelles inside nanoporous alumina membranes which were used for the synthesis of mesoporous silica hollow nanotubes and solid nanorods. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 54 publications
(74 reference statements)
0
27
0
1
Order By: Relevance
“…The interdigitated bilayer structure of CTAB-TOPO-coated CdSe/ZnS QD, whose first layer was original surface ligands TOPO and the second layer was CTAB, made it a more sensitive and selective fluorescence probe than CdSe/ZnS QD to the quenchers [46]. Similar organic coated bilayer structures of water-soluble CdSe/ZnS QDs were also investigated by others as fluorescence quenching probes for selective detection and quantification of analytes like chloride anion [47], hypochlorite [48], heavy metal ions [27][28][29][30]49], nitroaromatic [50] and even chiral mixtures of enantiomers [51,52].…”
Section: Comparison Of Oil-soluble Qds and Water-soluble Ctab-coated Qdsmentioning
confidence: 99%
“…The interdigitated bilayer structure of CTAB-TOPO-coated CdSe/ZnS QD, whose first layer was original surface ligands TOPO and the second layer was CTAB, made it a more sensitive and selective fluorescence probe than CdSe/ZnS QD to the quenchers [46]. Similar organic coated bilayer structures of water-soluble CdSe/ZnS QDs were also investigated by others as fluorescence quenching probes for selective detection and quantification of analytes like chloride anion [47], hypochlorite [48], heavy metal ions [27][28][29][30]49], nitroaromatic [50] and even chiral mixtures of enantiomers [51,52].…”
Section: Comparison Of Oil-soluble Qds and Water-soluble Ctab-coated Qdsmentioning
confidence: 99%
“…Several authors have published excellent well‐detailed protocols with descriptors for the preparation routes for QDs 32–34. In general, coatings on the CdSe QDs with higher bandgap materials is necessary, such as ZnS shells, in order to increase the photostability and luminescence properties of the resulting core–shell QDs 35. QDs made of CdSe/ZnS core–shell have been the preferred choice for bioapplications 22.…”
Section: How Are Quantum Dots Made?mentioning
confidence: 99%
“…Weaver et al for example studied the fluorescence quenching behavior during the incorporation of CdSe@ZnS NCs into cyanoacrylate, epoxy and silicone [46]. They found that excess of amines in the NCs solution passivated the NCs surface and preserved the PL QY of the NCs-polymer composites.…”
Section: Integration Of As Synthesized Semiconductor Ncs Into Polymermentioning
confidence: 99%